2012
DOI: 10.1021/jm201258k
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationship (SAR) Development and Discovery of Potent Indole-Based Inhibitors of the Hepatitis C Virus (HCV) NS5B Polymerase

Abstract: Starting with the indole-based C-3 pyridone lead HCV polymerase inhibitor 2, extensive SAR studies were performed at different positions of the indole core. The best C-5 groups were found to be compact and nonpolar moieties and that the C-6 attachments were not affecting potency. Limited N-1 benzyl-type substituent studies indicated that the best substitutions were fluoro or methyl groups at 2' or 5' positions of the benzyl group. To improve pharmacokinetic (PK) properties, acylsulfonamides were incorporated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 43 publications
0
33
0
Order By: Relevance
“…The peptide based derivatives (29) (IC 50 ¼ 70 nm), heterocyclic compounds like thiaphene dihydroxy pyrimidine derivatives (30, [57], thiaphene dihydroxy pyrimidine derivatives (31 & 32, IC 50 ¼ 0.14 & 0.15 mM) [57], thiazline dihydroxy pyrimidine derivatives (33, IC 50 ¼ 0.76 mM), were evaluated as HCV NS5B inhibitors (29 to 33) ( Fig. 11).…”
Section: Nucleoside Non-nucleoside and Protease Inhibitors As Anti-hmentioning
confidence: 99%
“…The peptide based derivatives (29) (IC 50 ¼ 70 nm), heterocyclic compounds like thiaphene dihydroxy pyrimidine derivatives (30, [57], thiaphene dihydroxy pyrimidine derivatives (31 & 32, IC 50 ¼ 0.14 & 0.15 mM) [57], thiazline dihydroxy pyrimidine derivatives (33, IC 50 ¼ 0.76 mM), were evaluated as HCV NS5B inhibitors (29 to 33) ( Fig. 11).…”
Section: Nucleoside Non-nucleoside and Protease Inhibitors As Anti-hmentioning
confidence: 99%
“…16 To rule out any bias, each of the five reported NS5B allosteric binding pockets TP-I (PDB ID: 2XWY), 11 TP-II (PDB ID: 3FRZ), 12 PP-I (PDB ID: 3TYV) 27 , PP-II (PDB ID: 3FQL), 14 and PP-III, that significantly overlaps with PP-II (large grid box created around PP-II bound HCV-796 to obtain docking pose at PP-III), was examined for inhibitor binding. Analysis of the binding energy data (Glidescores) for all single digit µM inhibitors at each allosteric site revealed that they bind with affinity in the order PP-I>PP-II>PP-III>TP-I>TP-II.…”
Section: Resultsmentioning
confidence: 99%
“…To gain insight into the molecular mechanism of inhibition, we analyzed the interactions of the docked conformation of compound L- 34 (panel A) and for comparison D- 45 (panel B) within the PP-I of NS5B (PDB ID: 3TYV) 27 as shown in Fig. 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that position 5 of the indole core was moreover very permissive in terms of nature and size, as methyl, ethyl, bromo, tert‐butyl, or cyclopropyl substituents all led to compounds exhibiting IC 50 below 10 nM. Finally, sulfonamide analogues induced an increase of activity, reaching an IC 50 of 3 nM for compound 38h . Interestingly, N −1 substitution with 2‐fluoro‐5‐nitrobenyl leads to a reaction between the phenyl ring and residue Cys366.…”
Section: Palm Pocket I Inhibitorsmentioning
confidence: 99%